Journal d'un collectionneur : marchand de tableaux - Gimpel, René 1881-1945 (Hermann, 2011)
The author of this paper is only in 1881. "It was an art dealer, son of art dealer, witness the revolutionary changes that, of the discovery of Cezanne, saw win the world a conception of art quite new." Rene Gimpel had inherited from a traditional approach to painting and he always showed a preference for the great masters of french mile century, including Chardin. But this does not prevent him from recognizing the genius, even under the mask of a new style: Braque, has his eyes, had reached the same perfection. Born into a family that had fled Alsace, outraged by the terms of the treaty of 1871, it was also animated by this spirit of revolt that led him to enlist, as his three son, in the Resistance. Internally by Vichy, and then arrested by the Germans, he was deported to Neuengamme where he died in January 1945, having prepared his fellow inmates to the Liberation teaching them English through virtual walks in the great museums of the world. Rene Gimpel begins to write in 1918. "The interest of the book is often beyond the little story or anecdote. Rene Gimpel himself knew how to see and watch. He has a sense of respect, his eye is a cartoonist and his log fills sketches and very personal. He knew everything, saw everything from painting for forty years, "sailing between America and Europe, helping to build the Atlantic the largest collections: those of Frick the Rockefellers, the Rothschilds, Ford, JP Morgan ... It mixes with the artists Braque, Cassatt, Forain which he relates the right words, Marie Laurencin, Matisse, Monet, Picasso, Renoir, he described the old painting with brush attachment to his outstretched arms, Soutine, Utrillo, but also merchants: Joe Duveen, his step-brother, Durand-Ruel, Paul Rosenberg, Nathan Wildenstein which he was associated, Ambroise Vollard ... It crosses writers and critics, Apollinaire, Berenson, and above all he met Marcel Proust, in 1907, Cabourg, where they were staying in the same hotel. Their common passion for the Vermeer formed a deep friendship